2022
DOI: 10.3390/ijgi11020074
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Urban Public Transport on Residential Transaction Prices: A Case Study of Poznań, Poland

Abstract: This study aims to determine the magnitude and nature of the impact of public urban transport accessibility on the value of residential properties in Poznań. The study was based on 2561 residential transactions completed within the study area in 2020. The input data obtained from the Board of Geodesy and Municipal Cadastre “GEOPOZ” were analysed statistically and spatially. The main part of both the spatial and the statistical analysis was performed using the hedonic pricing method (HPM)-OLS (ordinary least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…Based on the results of geographically weighted regression, the study has shown that the importance of the Pozna ń Fast Tram in terms of satisfaction with the place of residence is high, whereas the impact on home prices is relatively small. Another study, also in Pozna ń [26], has not revealed a statistically significant relationship between distance from bus stops and the price of housing. Similarly, the authors of [18] have proved that the Taiwan High Speed Rail has a negligible impact on house prices.…”
Section: Real Estate Value (Residential Prices)mentioning
confidence: 91%
See 1 more Smart Citation
“…Based on the results of geographically weighted regression, the study has shown that the importance of the Pozna ń Fast Tram in terms of satisfaction with the place of residence is high, whereas the impact on home prices is relatively small. Another study, also in Pozna ń [26], has not revealed a statistically significant relationship between distance from bus stops and the price of housing. Similarly, the authors of [18] have proved that the Taiwan High Speed Rail has a negligible impact on house prices.…”
Section: Real Estate Value (Residential Prices)mentioning
confidence: 91%
“…In later years, major transport infrastructure construction initiatives (motorway networks, high-speed railways, seaports and airports) were mainly observed in Asia, as well as in Central and Eastern Europe and on other continents, especially in developing countries. This gave rise to a number of publications in countries previously considered as developing ones, i.e., in Asia [7][8][9][10][11][12][13], India [14][15][16], Pakistan [17], Taiwan [18]; Armenia, Georgia and Turkey [19,20], Russia [21] or in the Middle East [22], as well as in Eastern Europe (in Poland [23][24][25][26][27][28][29][30][31] and Croatia [32]) and Southern Europe (in Greece [33,34], Spain [35], Portugal [36] and in Italy [37]). The increased interest in this research topic in the countries mentioned above was often linked to the parallel rapid socio-economic development of areas where transport infrastructure was being expanded.…”
Section: Introductionmentioning
confidence: 99%
“…Job accessibility was also found to affect housing choice and price [29]. Transportation such as metro/railway networks [30][31][32][33][34] and bus rapid transit networks [35] was also influential. Further, accessibility of quality schools strongly influenced price [36,37].…”
Section: Literature Review 21 Theoretical Review Of Hedonic Pricing M...mentioning
confidence: 98%
“…Several studies have found that transport infrastructure exerted a positive impact on land values; this is especially true for properties in close proximity to stations [10]. ´However, in some instances, urban transit projects could also produce negative impacts on land value usually as a result of factors such as noise, pollution or a rise in incidence of crime [21].…”
Section: The Impact Of Road Infrastructure Development On Land Value ...mentioning
confidence: 99%